Mixed Ionic‐Electronic Charge Transport in Layered Black‐Phosphorus for Low‐Power Memory. (23rd November 2021) - Ahmed, Taimur; Kuriakose, Sruthi; Tawfik, Sherif Abdulkader; Mayes, Edwin L. H.; Mazumder, Aishani; Balendhran, Sivacarendran; Spencer, Michelle J. S.; Akinwande, Deji; Bhaskaran, Madhu; Sriram, Sharath; Walia, Sumeet
Abstract: Availability of computing will be strongly limited by global energy production in 1–2 decades. Computing consumes 4–5% of global electricity supply and continues to increase. This is underpinned by memory and switching devices encountering leakage as they are downscaled. Two‑dimensional (2D) materials offer a potential solution to the fundamental problem owing to carrier confinement which significantly reduces scattering events. Herein, a mixed ionic‑electronic transport is used in layered black phosphorus (BP) based vertically stacked resistance change memories. The memory device relies on a unique interplay between the oxygen and silver ion diffusion through the stack which is generated using a combination of bottom (electrochemically active silver) and top (indium tin oxide) electrodes. The use of a transparent top‐electrode enabled for the first time to conduct spectroscopic characterization of the device and experimentally reveal fundamental mechanisms. Endurance of the devices are observed to be >10 4 switching cycles, with ON/OFF current ratio of >10 7 and standby power consumption of <5 fW, which effectively suppresses leakage current and sneak paths in a memory array. By undertaking detailed microscopic and spectroscopic investigations, supported by theoretical calculations, this work opens opportunities to enhance resistive switching performances of 2D materials for next‑generation information storage and brain‑inspired computation. Abstract : The use of 2D materials in resistance change memories offer a potential solution to challenges faced by next‐generation data storage technologies. Engineering mixed ionic‐electronic transport in 2D black phosphorus based vertically stacked memory addresses reliability and standby power consumption issues. Previously invisible localized switching spot is revealed nondestructively with high spatial resolution by a Raman mapping technique.